Breeding of Indian Spiny Loach, Lepidocephalichthys thermalis (Valenciennes, 1846) under Captive Conditions - Chaudhari, Ajit; Felix, Sugantham; Swain, Saroj Kumar; Uma, Arumugam (International Journal of Bio-resource and Stress Management, 2022)
The breeding of Indian spiny loach, Lepidocephalichthys thermalis was standardized under laboratory conditions at Madhavarm campus, Tamil Nadu Dr Jayalalithaa Fisheries University, Chennai, Tamil Nadu, India during May - August, 2014. Three different conditions were maintained in the breeding tanks which included gravel bed at the bottom with floating aquatic plants, gravel bed at the bottom without plants and soft sand layer bed at the bottom without plants. Spawning took place in the tanks provided with gravel bed at the bottom with and without plants. The eggs were transparent, adhesive and found attached to the plants and gravels. The incubation period ranged from 20-30 h at a temperature of 29.5°C. The newly hatched larvae were transparent with an average body length of 2 mm when observed microscopically. On day 1, larvae were thread- like with two external gill filaments on either side of the head and a pair of pectoral fin and a rounded caudal fin. On day 5, larvae developed four external gill filaments on either side of the head with prominent eyes, dark pigmentation with an average total length of 3.5 mm. On day 10, larvae had well-developed dorsal fin and a pair of anal fin. On day 10, larvae had an average total length of 13 mm with two pairs of barbels. Four weeks old larvae resembled the adults with an average total length of 20 mm. It is concluded that Indian spiny loach could be successfully bred in captive conditions by providing specialized spawning environment.